THE GENUS TEIJSMANNIODENDRON KOORDERS (VERBENACEAE) - KOSTERMANS, A. J. G. H. (Research Center for Biology, 1951)
Â 1. The present notes on Teijsmanniodendron are based on a study of the specimens from Herbarium Bogoriense and the Herbarium of the Singapore Botanic Garden. 2. The taxonomic value of the principal characters and their variation are discussed. Each of the species recognized is annotated.3. A delimitation and subdivision of the genus in two sections, Plurifoliolatae Kosterm. and Unifoliolatae Kosterm., is proposed. 4. A key to the 12 species and 1 variety distinguished, is included. 5. One new species is provisionally described (but not named), and one new variety, Teijsmanniodendron pteropodum var. auriculatum Kosterm., is published. 6. The following new combinations are made: Teijsmanniodendron coriaceum B. Clarke) Kosterm., T. hollrungii (Warb.) Kosterm., T. holophyllum (Bak.) Kosterm., T.novoguineense (Kan. & Hatus.) Kosterm., T. sarawakanum (H. H. W. Pears.)Kosterm., T. smilacifolium (H. H. W. Pears.) Kosterm., and T. subspieatum (Hallier f.) Kosterm.7.. The genus Xerocarpa H. 3. Lam (non Spach) is rejected; its only species,X. avicenniaefoliola H. J. Lam, is referred to Teijsmanniodendron ahernianum (Merr.)Bakh. In addition, the following reductions are made: Teijsmanniodendron monophyllum Kurata = T. hollrungii (Warb.) Kosterm.; Vitex bankae H. J. Lam = T.ahernianum (Merr.) Bakh., V. bogoriensis H. J. Lam = T. ahernianum (Merr.) Bakh.;V. koordersii H. J. Lam t= T. pteropodum (Miq.) Bakh.; V. tetragona Hallier f. =T. sarawakanum (H. H. W. Pears.) Kosterm.; V. venosa H. J. Lam = T. coriaceum (C. B. Clarke) Kosterm. Possible identity of T. longifolium (Merr.) Merr. and T.bogoriense is suggested: the identity of T. simplicifolium Merr. and T. smilacifolium(H. H-, W. Pears.) Kosterm. is indicated as probable.8. Vitex subspicata Hallier f. and V. holophylla Bak., included by Lam in Vitae hollrungii Warb., are reinstated as distinct species of Teijsmanniodendron.